2022
DOI: 10.1007/s12471-022-01680-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of post-percutaneous coronary intervention diastolic pressure ratio

Abstract: Aim To evaluate the distribution of a generic diastolic pressure ratio (dPR) after angiographically successful percutaneous coronary intervention (PCI) and to assess its association with the 2‑year incidence of target vessel failure (TVF), defined as a composite of cardiac mortality, target vessel revascularisation, target vessel myocardial infarction and stent thrombosis. Methods The dPR SEARCH study is a post hoc analysis of the prospective single-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Since then, it is argued that maximal hyperaemia is essential in order to detect the smaller pressure gradients post-PCI, and the adoption of post-PCI physiological assessment is hampered by the increased procedural time and effort. However, the findings by Masdjedi et al [2] show that the easily available resting dPR also has prognostic value in the assessment of post-PCI results. In this respect, it is important to mention some pathophysiological mechanisms that could explain the association between abnormal resting pressure gradients and clinical outcomes.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Since then, it is argued that maximal hyperaemia is essential in order to detect the smaller pressure gradients post-PCI, and the adoption of post-PCI physiological assessment is hampered by the increased procedural time and effort. However, the findings by Masdjedi et al [2] show that the easily available resting dPR also has prognostic value in the assessment of post-PCI results. In this respect, it is important to mention some pathophysiological mechanisms that could explain the association between abnormal resting pressure gradients and clinical outcomes.…”
mentioning
confidence: 96%
“…Only in recent years have studies regarding the importance of functional assessment of CAD emerged, and clinical practice has slowly been adapting to a more physiology-guided approach. In this issue of the Netherlands Heart Journal, the article by Masdjedi et al [2] importantly adds to the current literature with a post hoc analysis of the FFR-SEARCH registry regarding the prognostic value of the resting diastolic pressure ratio (dPR) post-percutaneous coronary intervention (PCI). In their study, they found that approximately 15% of the patients with optimal angiographic PCI results had an abnormal post-PCI dPR (< 0.89).…”
mentioning
confidence: 99%
See 2 more Smart Citations